PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Thania Atika Pratiwi; Yusnaini Yusnaini; Ermadiani Ermadiani (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
This research is aimed to evaluate the influence of intellectual capital to the company’s performance which is shown by return on equity and return on assets on the telecommunication companies that listed in Indonesia Stock Exchange. The data collection technique method used in this research is documentation of annual financial statement which has been obtained from the official website of Indonesian Stock Exchange. The population of this research is telecommunication companies that listed in Indonesia Stock Exchange (IDX) in 2012-2017. The sample selection technique used is purposive sampling. Samples used in this research are 5 companies. The analysis method has been done is simple linear regressions. The result of this research shows that intellectual capital gives positive influence to the return on equity as well to the return on assets.